Open Course Ware (OCW) as Support to the Social and Collaborative Learning - Rodriguez Morales, G. (2016)
The Web 2.0 technologies have significantly increased the access and use of contents on the websites, in the field of Education OCW provide students, faculties and self-learners the opportunity to access the prestigious Universities in the world. The aim of this study is to propose the integration of social technologies in the cycle of production and publishing of OCW in order to enhance the social and collaborative learning. The proposal is based on the analysis of literature review and application of quantitative and qualitative methods in a case study, the level of acceptance and expectations of integrating social technologies in Open Educational Resources (REA). The obtained results are a social and collaborative production cycle (REACS) complemented by social technologies implemented to Educommons platform to promote access, use and collaboration of this kind of resources. The case study and its implementation conclude that it is possible to enhance the social and collaborative learning in Open Course Ware